Job Stressors from Clinical Nurses’ Perspective - Torshizi L. MSc (نشریه پرستاری ایران, 2011)
Background & Aim: Nursing by its very nature is subject to high degrees of stress and is very important because of its relation with human’s life. The aim of the present study is determining job stressors from within clinical nurses’ perspective.   Material & methods: It was a descriptive cross-sectional study. The participants were 68 nurses working in two public hospitals in Tehran that were recruited by convenience sampling. Data was collected by nurses job stress Questionnaire and analyzed using SPSS-PC.   Results: The highest mean score in four dimensions of nurses’ job stressors were determined. In managerial dimension it was related to low salaries (3.40 ± 0.83) in work place conditions dimension, it was related to ward noise and overcrowding (3.38 ± .93), and in patient care dimension, it was related to presence of visitors out of official time(3.29 ± 0.89). Among four dimensions the mean score for managerial dimension was the highest (2.49±0.76)   Conclusion: regarding the importance of managerial stressors, nurse managers need to consider and modify these stressors in clinical settings of Tehran.